The politics of modern Central America : civil war, democratization, and underdevelopment - Lehoucq, Fabrice Edouard, 1963- (Cambridge University Press, 2012)
"This book analyzes the origins and consequences of civil war in Central America. Fabrice Lehoucq explains why the inability of autocracies to reform led to the civil wars of the 1980s and why violent conflict led to the unexpected transition to non-military governments in the 1990s. He examines why economic stagnation throughout much of the region, along with unevenness of political reform, has limited democratization. This book also uses these developments to shed light on core debates in comparative politics, suggesting that more progress has been made in understanding the persistence of inequality than in identifying the causes of civil war"--